2005
DOI: 10.1111/j.0022-202x.2005.23780.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Protein Kinase D During Differentiation and Proliferation of Primary Mouse Keratinocytes

Abstract: Diseased skin often exhibits a deregulated program of the keratinocyte maturation necessary for epidermal stratification and function. Protein kinase D (PKD), a serine/threonine kinase, is expressed in proliferating keratinocytes, and PKD activation occurs in response to mitogen stimulation in other cell types. We have proposed that PKD functions as a pro-proliferative and/or anti-differentiative signal in keratinocytes and hypothesized that differentiation inducers will downmodulate PKD to allow differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…Similar to our results, siRNA-mediated PKD1 knockdown in human keratinocytes resulted in increased involucrin mRNA expression [24]. Also, we have previously reported that PKD overexpression with an involucrin promoter reporter constructs results in decreased promoter activity [21]. …”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Similar to our results, siRNA-mediated PKD1 knockdown in human keratinocytes resulted in increased involucrin mRNA expression [24]. Also, we have previously reported that PKD overexpression with an involucrin promoter reporter constructs results in decreased promoter activity [21]. …”
Section: Discussionsupporting
confidence: 90%
“…2B) levels. These results are in line with the fact that in the epidermis loricrin is expressed in the upper granular layer where the calcium concentration is high [48] and where PKD1 levels are low [21, 49]. However, basally loricrin expression was not affected by the presence or absence of PKD1.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations